Prospective non-interventional multicentre observational trial of first-line anti-cancer treatment in patients with metastatic renal cell cancer in Belgium. Issue 5 (October 2014) - Cornelis, N.; Vermassen, T.; Schallier, D.; Machiels, J.-P.; Gil, T.; Debruyne, P. R.; D'hondt, R.; Bols, A.; Schrijvers, D.; Mebis, J.; Lumen, N.; Rottey, S.
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: Renal cell carcinoma (RCC) accounts for 2·4% of all new cancers in Belgium. Over the past decade, the armamentarium for systemic therapy of metastatic RCC (mRCC) has undergone important changes with implementation of targeted therapies directed against pathways involved in the pathogenesis of RCC. We describe first-line treatment choice of a group of patients in 9 Belgian oncology centres between October 2009 and November 2012. Methods: A clinical report form was established to assess patient characteristics, Karnofsky performance score, Memorial Sloan-Kettering Cancer Center risk criteria (MSKCC) and first-line therapy of mRCC patients. Choice of therapy and starting dose was analyzed before and after reimbursement of pazopanib in Belgium. Results: Ninety-six patients were eligible for the study. Non-smokers accounted for 53% of the patients. Seventy-three per cent of the patients had 0 or 1 MSKCC criteria in the group of patients that started treatment more than 1 year after initial diagnosis. In the group of patients that started therapy less than 1 year after diagnosis, 85% had 2 or more MSKCC criteria. This difference was statistically significant (P<0·0001). Overall distribution of the first-line therapies consisted of 43% sunitinib, 33% pazopanib, 14% temsirolimus, 7% everolimus and 3% sorafenib. Seventeen (18%) out of 96 patients started at a reduced dose level. Conclusion: This report shows that the guidelines for the start of first-line treatment in mRCC in 9 centres in Belgium were applied most of the time: a tyrosine kinase inhibitor was the first treatment choice for most patients while temsirolimus was an option for poor prognosis patients. In the majority of patients standard dose levels were initiated, although in some patients adaptation of dosage/treatment schedule was recorded.